Surface Meltwater Impounded by Seasonal Englacial Storage in West Greenland. Issue 19 (7th October 2018) - Kendrick, A. K.; Schroeder, D. M.; Chu, W.; Young, T. J.; Christoffersen, P.; Todd, J.; Doyle, S. H.; Box, J. E.; Hubbard, A.; Hubbard, B.; Brennan, P. V.; Nicholls, K. W.; et al.
Abstract: The delivery of surface meltwater through englacial drainage systems to the bed of the Greenland Ice Sheet modulates ice flow through basal lubrication. Recent studies in Southeast Greenland have identified a perennial firn aquifer; however, there are few observations quantifying the input or residence time of water within the englacial system and it remains unknown whether water can be stored within solid ice. Using hourly stationary radar measurements, we present observations of englacial and episodic subglacial water in the ablation zone of Store Glacier in West Greenland. We find significant storage of meltwater in solid ice damaged by crevasses extending down to 48 m below the ice surface during the summer, which is released or refrozen during winter. This is a significant hydrological component newly observed in the ablation zone of Greenland that could delay the delivery of meltwater to the bed, changing the ice dynamic response to surface meltwater. Plain Language Summary: Surface meltwater can drastically modify how glaciers flow. Depending on how and when it is delivered, meltwater can cause variable motion by modulating friction at the ice sheet base. Englacial water can control this behavior by either preventing water from reaching the bed or by delaying its release. In this paper, we present detailed observations of water storage within and at the bed of Store Glacier in West Greenland using hourly stationary ice penetrating radar measurements. In contrast to the previously discovered firn aquifer in high‐accumulation regions, at Store Glacier englacial water is present within a region of solid, damaged ice and persists until winter. This type of water storage has not been previously observed in solid ice and could explain some of the complex flow behavior of some Greenland glaciers. Key Points: Englacial water storage was observed in damaged solid ice with a phase‐sensitive radar in the ablation zone of Store Glacier, West Greenland Englacial water storage, intercepting a portion of surface meltwater, may contribute to the observed variability in glacial flow behavior Coincident periodic subglacial drainage events indicate an active subglacial drainage network beneath the englacial storage